BEBERAPA PARAMETER BIOLOGII KAN KUNIRAN (Upeneus sulphureus) HASIL TANGKAPAN CANTRANG YANG DIDARATKAN DIBRONDONG JAWA TIMUR [Biological parameters of the goat fishes, Upeneus sulphureus, caught by danish seine landed atBrondong, East Java] - Bambang Sumiono; Siti Nuraini (Jurnal Iktiologi Indonesia, 2007)
Study on relationships between length and weight, total length (TL) and fork length (FL), total length and standard length (SL) of goat fishes, Upeneus sulphureus was carried out based on length frequency data. Data was collected from March to May 2006 in fisheries landing place at Brondong, East Java. The total length-weight relationship of U. sulphureus follows the equation of W = 0.144 LJ J”. It means that increasing the length of goat fish was faster than their weight. The relationship between FL and TL follows the equation of FL = 0,9429 TL - 0.1899; relationship between SL and TL is SL = 0.4889 TL - 0.2938, and between SL and FL is SL = 0.8887 FL - 0.0984. The sex ratio of samples of fish captured by danish seine were male/female = 1 : 2.79. More than 50% of males and females were immature. The length at first capture by danish seine was found to be 13.3 cm TL. The catch composition and fishing seasons provide additional information on the goat fisheries biology landed in Brondong, East Java.